Suretyship in the Teaching of Ben Sira (Sir 29:14–20) - Andrzej Piwowar (The Biblical Annals)
The article is an analysis of the teaching of Ben Sira on becoming surety for individuals in need of that form of economic and material assistance contained in Sir 29:14–20. First, the way of functioning of suretyship in Israel and the approach to it is discussed, mainly based on the Book of Proverbs, which quite strongly and emphatically forbids that practice. This is followed by a delimitation of the pericope in the work of Ben Sira devoted to that issue and the presentation of its structure. The main part of the article is devoted to the exegetical analysis of Sir 29:14–20 based on the historical-critical method, taking into account elements of syntactic and semantic analysis. Ben Sira does not forbid becoming surety for those in need of such support; on the contrary, he encourages it (cf. 29:14a, 20a). However, influenced by abuses of that practice (cf. 29:16–19), he urges his disciple to be cautious and become surety only for acquaintances – neighbours (cf. 29:14a, 20a), not to risk and become bankrupt (cf. 29:16a, 17a, 20b) or be forced to leave the home country in case the borrower (cf. 29:18), for whom one had vouched, does not pay the obligations to the creditor. At the same time, Sirach reminds the person for whom someone has vouched of the need to fulfil the obligation towards the guarantor (cf. 29:15) as not doing so means becoming a sinner (cf. 29:16a, 19a). The main motive for Ben Sira’s change in approach to suretyship, in relation to the Book of Proverbs, seems to be primarily drawing attention to the commandment to help one’s neighbour, to which the Sage refers implicitly, and the desire to protect the Jewish community and strengthen it economically at a time when Hellenistic influence on it was increasingly stronger and more significant.